Morphology of the pollen of the Acanthaceae, Vitaceae and Violaceae families of the Mexico Valley - Palacios-Chavez, Rodolfo; Arreguin-Sanchez, Maria de la Luz; Quiroz-Garcia, David Leonor (Instituto de Ecología, A.C., 1996)
Pollen grain morphology of the families Acanthaceae, Vitaceae and Violaceae of the flora of the Valley of México is studied and illustrated: the first family is represented by Acanthus mollis L., Anisacanthus quadrifidus (Vahl) Standl., Dicliptera peduncularis Nees, Dyschoriste decumbens (Gray) O. Ktze., D. microphylla (Cav.) O. Ktze., Justicia furcata Jacq., Pseuderanthemum praecox (Benth.) Leonard, Ruellia bourgaei Hemsl., R. lactea Cav., R. speciosa (Nees) Lindau, Stenandrium dulce (Cav.) Nees and Tetramerium nervosum Nees.